New Chillicothe, Dickinson County - Nuss, Alex (Kansas State University, The Chapman Center for Rural Studies, 2011)
Calling New Chillicothe a “Lost Town” may be stretching the imagination a little bit. New Chillicothe was a postal station located in Sherman Township in northern Dickinson County. This station moved a total of four times in a matter of 28 years.
Alex Nuss, “New Chillicothe, Dickinson County,” Chapman Center Research Collections, accessed October 26, 2020, https://ccrsresearchcollections.omeka.net/items/show/41.
Keywords: Bethany United Methodist Church; Dickinson County; New Chillicothe; Paul Hoover land; Sherman Township; Caughron Saw Mill